2012
DOI: 10.1111/j.1365-2109.2012.03174.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of docosahexaenoic acid on growth, survival and swim bladder inflation of larval amberjack (Seriola dumerili, Risso)

Abstract: The effect of docosahexaenoic acid (DHA) on the growth performance, survival and swim bladder inflation of larval Seriola dumerili during the rotifer feeding period was investigated in two feeding experiments. Amberjack larvae at 3 day post hatching were fed rotifers enriched with (1) freshwater Chlorella (Chlo), (2) a mixture (2:1, v/v) of Chlo and DHA-enriched Chlorella (DHA-Chlo), (3) DHA-Chlo and (4) DHA-Chlo and commercial DHA emulsion, in triplicate for 7 days. The average DHA contents of the rotifers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 40 publications
3
31
0
3
Order By: Relevance
“…Docosahexaenoic acid is one of the main n‐3 LC‐PUFAs, which is significant to fish development (Matsunari et al, ). M. amblycephala is one of the most commonly eaten freshwater fish in China (Fisheries Bureau & Ministry of Agriculture of China, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Docosahexaenoic acid is one of the main n‐3 LC‐PUFAs, which is significant to fish development (Matsunari et al, ). M. amblycephala is one of the most commonly eaten freshwater fish in China (Fisheries Bureau & Ministry of Agriculture of China, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the effect of DHA was superior to EPA in the growth of some larval fishes (Emery, Norambuena, Trushenski, & Turchini, ; Takeuchi, Arakawa, Satoh, & Watanabe, ; Wu, Ting, & Chen, ). DHA is one of the main n‐3 LC‐PUFAs, which could promote normal growth, survival rate and swim bladder inflation of larval fish (Campoverde & Estevez, ; Matsunari et al, ). Feeding diets deficient in DHA showed growth retardation, and diets supplemented with DHA significantly increased the growth of fish (Bransden, Battaglene, Morehead, Dunstan, & Nichols, ).…”
Section: Introductionmentioning
confidence: 99%
“…Kandungan lemak rotifer yang cukup tinggi di semua perlakuan dipengaruhi oleh penambahan minyak ikan pada saat pengkayaan sebagai sumber asam lemak n3-highly unsaturated fatty acids, terutama 22:6n-3. Asam lemak tersebut sangat esensial bagi ikan kerapu (Wu et al, 2002) dan ikan laut lainnya, seperti larva amberjack Seriola dumerili, karena dapat meningkatkan pertumbuhan, sintasan dan perkembangan gelembung renang (Matsunari et al, 2013). Namun, kadar lemak rotifer yang tinggi belum mampu secara maksimal memberikan energi berlebih kepada larva untuk mengkonsummsi rotifer.…”
Section: Hasil Dan Pembahasanunclassified
“…Namun, untuk meningkatkan pertumbuhan dan sintasan larva ikan amberjack Seriola dumerili dibutuhkan taurin sebanyak 800 mg/l media pengkaya (Matsunari et al, 2013), untuk larva Japanese flounder Paralichthys olivaceus sebanyak 400 mg.L -1 media pengkaya (Chen et al, 2005), dan untuk larva udang Litopenaeus vannamei sebesar 50 mg.L -1 (Jusadi et al, 2011). Perbedaan dosis taurin di antara dua spesies ini bisa menjadi pertimbangan dalam menentukan dosis optimal taurin untuk pengkayaan rotifer sebagai pakan species larva ikan lain.…”
Section: Hasil Dan Pembahasanunclassified
“…Unlike saturates and monoenes, which can be synthesized by most vertebrates, including marine fish, LCPUFA cannot be produced (or are produced in very limited amounts) and their needs are mostly covered by their food intake. Amongst most important LCPUFA fatty acids, those belonging to the n-3 series (n-3 LCPUFA) and n-6 series (n-6 LCPUFA) are considered essential (Sargent et al, 1995; Díaz and Marín, 2013; Spector and Kim, 2015), and their deficiency are associated with a number of pathophysiological conditions and with the failure in adaptive responses (Bell et al, 1986; Gerbi et al, 1993, 1994, 1998; Sargent et al, 1995; Bogdanov et al, 2008; Russo, 2009; Díaz and Marín, 2013; Matsunari et al, 2013). …”
Section: Introductionmentioning
confidence: 99%